Design, Control and Monitoring of an Offline Mobile Battery Energy Storage System for a Typical Malaysian Household Load Using PLC - Nabil Mohammed; Kumeresan A. Danapalasingam; Ahmed Majed (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
Battery energy storage system (BESS) is used in many practical applications including uninterruptible power supplies (UPS), portable devices, electrical vehicles and renewable energy systems. To utilize BESS effectively, an efficient control operation is required. Various controllers have been introduced in the open literature. However, they are not considered the best fit due to their limitations. This includes their incapability of handling high-power rating BESS, low noise immunity, short life cycle and limited number of input and output interfaces. In this paper, the programmable logic controller (PLC) is used to control and monitor a 158.8 kWh offline BESS for a typical Malaysian household. TIA Portal V13 software by siemens is used to program the proposed PLC control. Human machine interface(HMI) system is used to monitor and simulate the control performance. The results show that the PLC approach provides an efficient and reliable control of the BESS in which a compact protection against the battery overcharging, under-discharging and overheating is achieved.